The microbial burden in chronic suppurative otitis media patients along with their antibiogram - R Sharma, Shweta; Singh, Sudhir; Mishra, Amit; Singh, Prachi (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Chronic suppurative otitis media (CSOM) is a common health problem in countries with low socio-economic strata because of poor nutrition, population burden, low hygienic condition, insufficient health care, and repeated upper respiratory tract infection (URTI). Untreated cases of CSOM result in complications ranging from persistent otorrhoea, mastoiditis, labyrinthitis, facial nerve palsy to intracranial abscesses or thromboses. Microbiological profile and their antibiotic sensitivity pattern are essential to enable proper treatment of this disease and preventing the development of complications. Material and Methods: The current study was designed to identify the pathogenic agents causing CSOM and to understand their antimicrobial resistance pattern who attended ENT Department of this hospital between July 2017 to June 2019. Results: Among 496 clinical samples, microbes were seen in 329 (66.3%) cases with predominant male (66.3%) distribution and age group of 11-20 years (31%). Pseudomonas spp. (50.7%) is predominantly isolated. It showed resistance to aminoglycosides and fluoroquinolones but was found sensitive to carbapenems with a resistance rate of 1.2%. ESBL (Extended-spectrum β- lactamase) detection was seen in 30.9% of GNB while MBL (Metallo β- lactamase) was detected in 2.7% of cases. S.aureus was highly resistant to first-line antibiotics with MRSA (Methicillin-resistant S.aureus) rate of 64.1%, however, all were sensitive to glycopeptides. Conclusions: There should be a minimum gap between the onset of symptoms and the treatment provided to prevent complications of CSOM and also the complicated cases should be referred to specialized centers for better management.